(untitled) (Ricos Biology, 2025)
The escalating crisis of antimicrobial resistance (AMR) threatens to unravel a century of medical progress. Conventional antibiotics, with their specific, single-target mechanisms, are increasingly rendered ineffective, necessitating the urgent development of novel therapeutic strategies. Antimicrobial Peptides (AMPs), fundamental components of the innate immune system across all kingdoms of life, have emerged as promising candidates. A pivotal advantage of AMPs over traditional antibiotics is the perceived difficulty for microbes to develop robust resistance against them. This review delves into the mechanistic underpinnings of this phenomenon, exploring the unique mode of action of AMPs, the fitness costs associated with resistance mechanisms, and the evolutionary trade-offs that constrain microbial adaptation. While acknowledging that resistance is not impossible, we argue that the inherent properties of AMPs present a significantly higher and more complex barrier for resistance development compared to conventional drugs.